The submission, cultural trauma of America and its Muslim community after 9/11 - Jabarouti, Roya; Mani, Manimangai (Scottish Group, 2014)
Although the post-9/11 decade has reached a total closure, Americans and the world in general are still trying to come to terms with the aftermath of 9/11/2001. While in comparison to other acts of terrorism around the world, the economic and political effects of the attacks were minuscule, the emergence of post-9/11 literature discloses its wide cultural impact. The Submission (2010), a novel by Amy Waldman, is distinctive for exploring the historical origins of a wound that almost permanently split the united multiculturalism of America. It narrates a prolonged controversial process in which the vestiges of cultural trauma are embedded in American history. This study therefore uses the theory of cultural trauma and employs a close reading of the selected text on the states of multicultural and multi-religious American characters, Muslim-Americans in particular, with regards to the social-cultural aftermath of 9/11. It shows the socio-historical elements and the agencies involved in the establishment of this collective trauma, as well as in the process of selecting a coping strategy among each collectivity. Finally, it reveals that by megasizing the memorial, cultural carriers not only increase the ambiguity over the reality of the event, but also delay the process of social recovery. Deaths and births of cultures occur in the construction of collective trauma; although The Submission(2010) carries the past within a fictional frame, it presents a new perspective that is impervious towards blind submissions of any sort.